Fatigue life of an anchored blind-bolt loaded in tension - Tizani, Walid; Abd Rahman, Norashidah; Pitrakkos, Theodoros (Elsevier, 2014)
This paper investigates and reports on the fatigue behaviour of a novel blind-bolt system termed the Extended Hollo-bolt (EHB). The new blind-bolt is a modified version of the standard Lindapter Hollo-bolt, and its application relates to the construction of bolted, moment-resisting connections between open profile beams and concrete-filled tubular columns. The fatigue behaviour of the system is studied on the basis of constant amplitude loading tests, with a total of 56 experiments being reported. The specimens were subjected to tensile loading for various stress ranges, with the repeated load being selected relative to the design yield stress of the blind-bolt's internal shank. The influence of testing frequency and strength of concrete infill is also examined. An analysis of the results indicates that an increase in the concrete strength can increase the fatigue life of the EHB system. Within the tested range, the failure mode of the EHB under repeated loading was found to be due to internal bolt shank fracture, a mode which is consistent with its monotonic behaviour and also comparable with standard bolt–nut–washer system behaviour. The experimental results (S–N data) were further compared with the Eurocode 3 Part 1-9 guidelines. The fatigue design strength of the anchored EHB blind-bolt is found to be adequately represented by the current specification detail Category 50 that is provided for standard bolting systems.